Non-surgical nursing care for tumor patients: an overview of sedation, analgesia, and recent innovations - Wei, Wei; Wang, Pan; Qing, Pan; Li, Zhang; He, Qi (Frontiers in Oncology, 2024)
With the increasing prevalence of tumors, effective symptom management has emerged as a cornerstone of patient care. While surgical interventions remain pivotal, non-surgical nursing methods have gained prominence in providing relief from pain, discomfort, and other tumor-related symptoms. This review delves into the various non-surgical approaches employed, emphasizing tumor sedation and analgesia. We discuss the array of non-pharmacological and pharmacological strategies, shedding light on their indications, contraindications, and potential side effects. Furthermore, the importance of addressing individual differences in pain perception and the ethical considerations in symptom management are highlighted. We conclude by providing insights into the recent innovations in the field, emphasizing the need for personalized and comprehensive care to enhance patients’ quality of life. Tumor sedation, Tumor analgesia, Non-surgical nursing care, Pain management, Non-pharmacological interventions, Palliative care, Recent innovations, Symptom management.